PEMANFAATAN GOOGLE PARENTAL CONTROL UNTUK MENGAWASI KEGIATAN TELEPON PINTAR PADA ANAK - Suhartini, Andi Mulyanti; Bhakti Herwidyaningtyas , Frestina (LPPM ISTeK ICsada Bojonegoro, 2024)
The implementation of Community Service is a socialization of information delivery to Parents in monitoring children's smartphones with an age range of 6-12 years using Google Parental Control. With the ability of parents to use and utilize the Family Link application on Google, the ease of utilizing Parental Control will run well and make it easier to organize and filter content or games that are considered inappropriate for the age of the child as a user. The purpose of utilizing Google Parental Control to monitor activities on children's smartphones is that parents are able to regulate the time of use on children's smartphones, duration of use, and filter content or sites that are not suitable for children's age as users at SDN Sumurjalak II, Plumpang District, Tuban Regency, East Java Province. The results of this study are the ability of parents to apply the information that has been conveyed and are able to carry out maximum supervision of smartphones in children from the negative influence of uncontrolled technological developments and control the duration of smartphone use in children.